(untitled) (Международный научный журнал «Инженер», 2026)
This scientific article analyzes the forces that occur in belt drives and their impact factors. Belt tension, wheel diameters, and rotational speed are considered as input factors in the study. The moment transmitted through the transmission and the dynamic loads acting on the belt are studied as output factors. The relationship between these factors is expressed using mathematical modeling and optimal working conditions are determined. The main purpose of the study is to determine the optimal parameters for improving the efficiency of belt drives and ensuring their reliability.